NEUROSCIENCE DALAM KEGIATAN BELAJAR SISWA DI SEKOLAH - Fathullah Munadi; Rahmat Shodiqin, Trining Puji Astutik, Agustina Ambar Pertiwi, Ika Irayana (CV. ADIBA AISHA AMIRA, 2023)
Neuroscience is the science that specifically studies neurons (nerve cells). Meanwhile, learning neuroscience is the science of the relationship between the nervous system and learning and behavior. It can be seen that the brain is divided into four, namely: first, Cerebrum or big brain, Cerebrum is the largest part of the human brain which is also called the Cerebral Cortex, Forebrain or Forebrain. The cerebrum is the part of the brain that distinguishes humans from animals. The cerebrum makes humans have the ability to think, analyze, logic, language, awareness, planning, memory and visual abilities, which the ability to think is an important aspect of student learning not only at school, but in personal life.